A different kind of power : a memoir - Ardern, Jacinda, 1980- (Crown, 2025)
"What if we could redefine leadership? What if kindness came first? Jacinda Ardern grew up the daughter of a police officer in small-town New Zealand, but as the 40th Prime Minister of her country, she commanded global respect for her empathetic leadership that put people first. This is the ... story of how a Mormon girl plagued by self-doubt made political history and changed our assumptions of what a global leader can be."--